2013
DOI: 10.2737/pnw-gtr-881
|View full text |Cite
|
Sign up to set email alerts
|

Changes in land use and housing on resource lands in Washington state, 1976–2006

Abstract: Changes in human land use patterns have wide-ranging social, economic and ecological implications. How urban and residential areas develop to accommodate population increase can have varying effects on forest and agricultural production from resource lands. Estimates of the amount and type of land use change differ substantially with definitions and analytical methods used. The purpose of this study was to apply a robust manual image classification method to assess changes in land use and housing density acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The data consist of geo-referenced point observations of discrete land-use classes observed on nonfederal lands from photo-interpretation of a systematic-random grid of points located on aerial photographs for 1974for , 1984for , 2000for , 2005for , and 2009for in Oregon, and 1976for , and 2006 for Washington, at a sampling density of one point per 187 ha (e.g., Gray et al, 2013). Land-use classes include wildland forest, mixed forest-agriculture, intensive agriculture, low-density residential, and urban (Fig.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The data consist of geo-referenced point observations of discrete land-use classes observed on nonfederal lands from photo-interpretation of a systematic-random grid of points located on aerial photographs for 1974for , 1984for , 2000for , 2005for , and 2009for in Oregon, and 1976for , and 2006 for Washington, at a sampling density of one point per 187 ha (e.g., Gray et al, 2013). Land-use classes include wildland forest, mixed forest-agriculture, intensive agriculture, low-density residential, and urban (Fig.…”
Section: Datamentioning
confidence: 99%
“…Historical land-use data spanning 1974-2009for Oregon and 1976-2006 for Washington were compiled by the Oregon Department of Forestry and USDA Forest Service's Forest Inventory and Analysis Program, Pacific Northwest Research Station (Gray et al, 2013;Lettman, 2011Lettman, , 2013. The data consist of geo-referenced point observations of discrete land-use classes observed on nonfederal lands from photo-interpretation of a systematic-random grid of points located on aerial photographs for 1974for , 1984for , 2000for , 2005for , and 2009for in Oregon, and 1976for , and 2006 for Washington, at a sampling density of one point per 187 ha (e.g., Gray et al, 2013).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the US National Oceanographic and Atmospheric Administration's Coastal Change and Analysis Program data showed that from 1992 to 2006, approximately 0.14% of the non-federal lands in Puget Sound were converted to a developed class each year. An independent Landsat-based study using data from 1986-2007 showed an annual rate of 0.5% of the land area changing to an urbanized class [55] while a US Forest Service study using 45,000 photo interpreted sample points, ranging from 1976 to 2006, found an annual new development rate of 0.38% [56]. Because land-use change in our study area over short time periods is spatially a rare event, typically acceptable land cover map accuracy rates of ~85% may be inadequate to effectively measure land cover change [57].…”
Section: Accuracy Optimizationmentioning
confidence: 99%
“…Some of the most remote areas of wilderness in the continental United States are found in the transboundary region of the Canadian‐United States border of the Pacific Northwest (Figure ). This area includes the North Cascades National Park Service Complex (NOCA), which provides valuable habitat for a number of species in an otherwise rapidly developing region (Gray, Azuma, Lettman, Thompson, & Mckay, ; Yeakley, Maas‐Hebner, & Hughes, ). The Skagit River is a key geographic and ecological feature in the western portion of the Park, connecting remote montane ecosystems to the Puget Sound and serving as a key wintering site for bald eagles ( Haliaeetus leucocephalus ), an apex predator that feeds in high densities on spawning of chum ( Oncorhynchus keta ), and coho ( Oncorhynchus kisutch ) salmon.…”
Section: Introductionmentioning
confidence: 99%